Ischemic Stroke in Infants and Children: Practical Management in Emergency - Sara Ciccone; Michela Cappella; Caterina Borgna-Pignatti (Stroke Research and Treatment)
Stroke is a rare disease in children, with an estimated incidence 13/100000 and a significant impact on morbidity and mortality. Clinical presentation and risk factors, present in almost half of pediatric patients, are not the same as in adults. The diagnosis of stroke in children is often delayed because signs and symptoms can be subtle and nonspecific. History and clinical examination should exclude underlying diseases or predisposing factors. Neuroimaging is crucial in defining diagnosis. Other tests might be necessary, according to the clinical picture. We present here the most recent practical directions on how to diagnose and manage arterial stroke in children, according to different international guidelines on the subject.